Marine microbial bioprospecting and bioactive bioproducts: seven decades of discovery and contemporary perspectives - Veluchamy, Chandra; Nallakaruppan, Nagaraj; Nachiappan, Kanagam; Sekaran, Manoj; Vartak, Riddhi Bharat; Zambare, Rutuja Balasaheb; Panneerselvam, Sathishkumar; Chandrasekaran, Rajasekaran; Sharma, Avinash; Thiagarajan, Kalaivani (Frontiers in Marine Science, 2025)
The marine ecosystem is one of the world’s largest reservoirs, with billions of species interacting. It harbors a diverse array of macro- and microorganisms equipped with unique metabolic abilities and intricate interactions enabling adaptation to challenging environments, resulting in the biosynthesis of secondary metabolites. The expanding field of marine (blue) biotechnology investigates various, frequently disregarded aquatic ecosystems as viable and sustainable sources of biomolecules and biomass to meet these social demands. With a focus on the identification and industrial significance of bioactive chemicals and bioproducts derived from microbes, this review endeavors to present an in-depth analysis of marine microbial bioprospecting. Marine microbial exploration has produced thousands of structurally unique metabolites over the past few decades, many of which have shown industrial or medicinal significance. Approximately 28,500 marine natural products including polysaccharides, peptides, polyketides, polyphenolic compounds, sterol-like products, and alkaloids, had been identified as of 2016. Owing to developments in synthetic biology and metagenomics, the frequency of discovery has significantly increased since the 2000s, and the present review systematically compiles these advancements using a PRISMA-based screening framework. In its entirety, this review emphasizes the critical ecological and biotechnological aspects of marine microorganisms and proposes a conceptual and quantitative foundation for further research into marine microbial resources in pharmaceutical development and sustainable biotechnology. The review was developed through a comprehensive literature search conducted using public databases.